Thermal Conductivity and Bending Strength of Coconut Fiber/Paraffin/Graphite Composite Phase Change Materials - Astika, I Made; Winaya, I Nyoman Suprapta; Ary Subagia, I Dewa Gede; Wirawan, I Ketut Gede (International Journal of Engineering and Emerging Technology, 2020)
The use of composite materials for panel boards, building construction, vehicle accessories, and household furniture is growing. Coconut coir fiber-reinforced composites can be applied as panel boards for building and furniture construction, which can also be used as heat storage systems. The coco fiber composite's low energy storage capacity can be increased by incorporating PCM material into it, forming a PCM composite material. Heat absorption and release performance depend on the material's thermal conductivity, which can be increased by adding additives such as graphite. This paper presents a performance test of PCM composites to obtain bending strength and thermal conductivity. The research materials were coconut coir fiber, polyester, paraffin, and graphite. The weight fractions of coco fiber and polyester were 30 and 50%, respectively. Variation of paraffin weight fraction 15 and 20% and variation of graphite weight 0 and 5%. The method of mixing materials is direct incorporation and forming of PCM composites using a press molding process. The tests carried out include the bending test (ASTM D790-03) and the thermal conductivity test using the Heat Transfer Experiment Base Unit test kit. The results show that the use of 15 wt% paraffin with 5 wt% graphite increases thermal conductivity by 23.27% and increases bending strength by 36.71%.